Airline Service Delays And The Impact On Customer Perceptions, Switching Intentions And Negative Word Of Mouth - Simarmata, Juliater; Ikhsan, Ridho Bramulya; Prabowo, Hartiwi; Yuniarty, Yuniarty; Wouter, Dewulf (Sekretariat Badan Kebijakan Transportasi, Kementerian Perhubungan, 2022)
This research examines the influence of service delay on negative emotions and its result on switching plans and negative word of mouth as customer behavior. The survey was conducted on customers who have undergone delays in LCC airlines in Indonesia. The respondents' total number was 383, and the questionnaire responses were analyzed using SEM and mediation testing. As a result, this study accepts all the hypotheses that service delay affects anger and worry, and its impact on switching intention behavior and negative word of mouth. This research provides insight into how airlines can manage and improve their service policies to minimize service delays.